Residual Hip Dysplasia in Children With Unilateral Hip Dislocation—Does Side Matter?. Issue 10 (6th November 2022) - Lin, Hsin-Ying; de Vos-Jakobs, Suzanne; Westerbos, Stijn; Reijman, Max
Abstract : Background: Developmental dysplasia of the hip (DDH) is the most common musculoskeletal abnormality in infants and young children. Despite the fact that the left hip is most frequently affected, literature and clinical experience suggest a poorer outcome for right-sided hip dislocation in DDH. On the basis of this hypothesis, we studied the outcomes (residual dysplasia, number of surgeries, and complication rate) of right-sided unilateral hip dislocation in comparison with left-sided unilateral hip dislocation in DDH up to 8 years follow-up. Methods: We identified all patients with unilateral hip dislocation at Erasmus MC Sophia Children's Hospital from 2002 to 2012, diagnosed with DDH before the age of 1 year and with a minimum follow-up of 8 years. The primary outcome was residual dysplasia (based on an acetabular index (AI) >18 degrees and center-edge angle of Wiberg (CEA) <15 degrees) at the age of 8 years. Secondary outcome measures were residual dysplasia at the ages of 1, 2, and 5 years, successful surgical reduction rates, additional surgery, and complication rates. Results: Out of a consecutive series of 555 patients, 298 could be included (17 males; median age at diagnosis 4.0 [IQR 3.0 to 5.5] months): 107 patients (35.9%) had right-sided unilateral hip dislocation. There was no significant difference in residual dysplasia between the unilateral left-sided and unilateral right-sided hip dislocation groups, respectively, at 1-year follow-up (34.0% vs. 24.2%, P =0.107), 2-year follow-up (74.1% vs. 70.1%, P =0.565), 5-year follow-up (74.1% vs. 66.2%, P =0.261), and 8-year follow-up (65.3% vs. 53.8%, P =0.199). There was no significant difference in surgical interventions between the left-sided and right-sided hip dislocation groups, respectively: additional surgical reduction (14.7% vs. 15.0%, P =0.945) and additional surgery for residual dysplasia (8.9% vs. 10.3%, P =0.695). There was no significant difference in complication rate between the unilateral left-sided and unilateral right-sided hip dislocation groups, respectively: avascular necrosis (19.4% vs. 15.9%, P =0.454) and redislocation (11.5% vs. 9.3%, P =0.561). Conclusions: The results of our study suggest that in patients with DDH, unilateral right-sided hip dislocation does not have poorer outcomes compared with unilateral left-sided hip dislocation during an 8-year follow-up. Level of Evidence: Level III – retrospective follow-up study.